Analisa Tingkat Kebisingan terhadap Karyawan di Lingkungan Kerja Kantor PT. Surveyor Indonesia Cabang Medan - Muhammad Fahmi Sahab; Muhammad Banjarnahor; Chalis Fajri Hasibuan (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2017)
Noise is all unwanted sounds to some degree cause hearing loss. In the operation of PT.Surveyor Indonesia laboratory operation using some machines that cause noise that disrupt the workers. From result of research of noise level happened 68.93-89.12 dB and already exceeded the threshold in accordance with regulation of KEP-48 / MENLH / 11/1996. From the results of questionnaires distributed with the number of respondents 30 people. Tested the validity, reliability, and multiple linear regression analysis. The result of validity test value 0.631-0.944 this value> from r table value 0.361 can be summed up all valid questions. The reliability test results of 0.601-0.908 this value> of the cronbach alpha value of 0.600 can be summed up all reliable questions. Result of linear regression analysis obtained equation Y = -0.321-0.031-X1 + 0.076X2 + 1.114X3. Where X1 = communication, there is a negative relationship, X2 = physiology, positive relationship occurs, X3 = Psychology positive relationship occurs. The results of double correlation analysis test R = 0.701 this shows a strong relationship between noise to communication, physiology and psychology. And the result of coefficient test of regresi together with test F, obtained F arithmetic 8,392 and F table 2,975 so F count> F table thus Ho rejected Ha accepted meaning there is influence signifikan between noise to communication, physiology and psikolgi worker.